Communication Strategies of Small Businesses in Ukraine - Yushchyshyna, Larysa Oleksiivna; Hulchak, Oleksandr Mykolaiovych (Scholarly Publisher ICSSH, 2024)
Small businesses in Ukraine play a crucial role in ensuring economic stability, job creation, and community support, particularly amidst the challenges of war and the COVID-19 pandemic. In response to these difficulties, businesses are compelled to develop effective communication strategies that enable them to adapt to changes, retain customer loyalty, and strengthen market positions. A communication strategy is a systematic tool that coordinates interactions with various audiences and helps achieve business objectives. Successfully implementing such strategies supports the survival and growth of small businesses in the modern context.
Keywords: Small business; communication strategy; 005:338.2